Use of biomass sericin as matrices in functionalized graphene/sericin nanocomposites for the removal of phenolic compounds - Amir Abdolmaleki (Heliyon, 2020)
The removal of phenolic compounds, a group of environmental pollution even at low concentrations, by the adsorption process has attracted considerable attention around the world. Still, the choice of an absorbent has proved to be a challenge. As a result, for the first time, functionalized graphene (FG)/sericin nanocomposites to be applied as an adsorbent to remove phenolic compounds from aquatic systems. Sericin, the by-product of the silk process, was naturally benign and economically available matrices, which used to preparation of FG/sericin nanocomposites. The FG was prepared with the reaction between graphite and maleimide, then sericin attached to FG sheets by the amidation reaction. Because of the abundance of chemically active functional groups on the surface of these FG/sericin nanocomposites have been found to be excellent for decontamination of water for phenolic compound removal applications.